Beyond Rational Choice Theory: Multifaceted Determinants of Participation in Palm Oil Sustainable Certification Amongst Smallholders in Malaysia - Ahmad Rizal, Ammar Redza; Md Nordin, Shahrina; Hussin, Siti Haslina; Hussin, Siti Rahayu (Frontiers in Sustainable Food Systems, 2021)
The demand for palm oil is steadily increasing where global consumption has reached 77 million metric tons or equivalent to 7kg of palm oil used by each person in the world annually. The production of palm oil, however, facing a sustainability issue where critics on deforestation and unsustainable conducts during the production are increasing. As a solution, the sustainable-certified scheme was established where the scheme such as RSPO and MSPO was responsible for overseeing sustainability practices amongst its members. Efforts are being made to ensure every stakeholder in the palm oil industry obtain sustainable certification including smallholders. Getting smallholders certified facing a tough challenge where only 30% of smallholders were certified despite the rigorous efforts made. Identifying smallholders’ determinants will help policymakers to strengthen policy in disseminating sustainability practices in the palm oil industry. The study looks beyond rational choice theory and developed a model based on elements of social structure and interaction. Quantitative approached through questionnaire survey were used in this study. Data collections involve 200 oil palm smallholders in Malaysia Four elements namely ‘Perceived Economic Benefit’, ‘Social Interaction’, ‘Shared Identity’ and ‘Discourse’ were found to have a significant impact on smallholder’s participation in palm oil sustainable certification. Implication and future recommendation were included in the concluding remark.